Planning for low income settlements in the Blaauwberg Administration Area - Katz, Jessica (School of Architecture, Planning and Geomatics, 2016)
A topic that has increasingly come to the fore in urban planning is the accommodation of those people residing in informal settlements, characteristically the lowest income earners and unemployed. Internationally, nationally and locally, there is a general surge of interest in urban planning towards accommodating low-income settlements adequately, and in formalising informal settlements, based on increasing recognition of peoples' legitimate right to land and security of tenure. Along with these trends, the challenges presented by the urbanisation of poverty that surfaces in informal settlements has become increasingly of interest to me as a researcher and student of planning, over the past few years. This mini-dissertation provides an opportunity to explore some of the social and technical issues that need to be resolved with regards to low-income settlements. Largely related to the background of the ANC government's popular promises of "Housing for All" and "Jobs for All", informal dwellers in South Africa expect to receive formal housing and tend only to accept such services as are associated with subsidised housing. However, poverty in urban environments is a deeper issue that exists when an individual's or household's access to income, infrastructure or services in inadequate to meet their basic needs. More than a lack of income, poverty exists for that section of the population who are unable to pay for basic services or access development opportunities (Van Ryneveld, Muller & Parnell, 2003). .. Increasing urbanisation of poverty presents a challenge to decentralized local government. Although informal settlements have finally become accepted as a local government responsibility, insitu upgrading is a politically driven and preferred response to informal settlements. Upgrading, wherever possible, appears to be a reactive approach by local authorities rather than a pro-active response to the reality of increasing informal settlement. There is little evidence that authorities are planning ahead for informal settlements. Current policy and housing strategies consider those settlements where people earn less than R3500 per month as low-income settlements. In this document, reference to low-income settlements encompasses those who earn less than R3500 per month as well as the unemployed. Poverty alleviation has gradually become a primary political focus in Cape Town, manifesting in informal settlements eventually being allocated a substantial budget, as recently as 2003. This project is based on an extensive literature review that includes internal reports of city officials engaged in current upgrading of informal settlements initiatives of the City of Cape Town, as well as the ongoing debates surfacing in newspaper articles. Access to data gathered from field visits and on-site observations, attending public participation meetings and interactions with officials and their appointed consultants, has broadened insight with regards to low income settlement upgrading. The first section of this document provides the contextual background to the existing situation of low-income settlements in South Africa, and more specifically Cape Town. An analysis of economic opportunities, institutional and servicing issues that are associated with low-income settlements informs this background. As approaches to low income settlements in South Africa are still largely based at the national and provincial levels of government, rather than at the local metropolitan level, this section illustrates the shaping of the initiatives that are in place at a site-specific level. Section 2 comprises a site-specific analysis of the northern suburbs of Cape Town. The N1 and Salt River canal in the South, the N7 in the East, and the Atlantic Ocean in the West are the boundaries of the selected study area. To the North the study area extends to Philadelphia Road and Brakkefontein Road, including Koeberg. For details, refer to the locality map 1 below. The most recent 'Blaauwberg Spatial Development Plan', compiled by Planning Partners (2002) is used as a reference, along with various other Framework plans and proposals. Additional information is gathered from GIS and from current newspaper articles reporting on developments, debates and perspectives. In order to construct proposals on how to intervene in the study area so as to accommodate low income settlements in a more sustainable and integrative way, theory and case studies that provide precedent on approaches to low income settlements allows for drawing on a number of lessons that can be applied to the site. This will be the focus of Section 4. As the outcome of all the above sections, an improved approach and strategy for upgrading low-income settlements is suggested. The pre-empting of problems associated with foreseen increases in low-income settlements is put forward in the proposition that identifying and planning land most suitable for accommodating low-income settlements is an essential component of an effective strategy. As no proposal is complete without taking implementation into account, this will be dealt with in Section 5 through identifying a number of actions that would need to be carried out in order for such a proposal to be implemented.